Fecundity and Embryonic Development of Spiny Dogfish in the Northwest Atlantic Ocean. Issue 1 (25th October 2018) - Dutton, Jessica; Gioia, Kaitlyn A.
Abstract: We investigated the fecundity and embryonic development of Spiny Dogfish Squalus acanthias (68.8–88.4 cm TL; n  =   49) caught in the northwest Atlantic Ocean off Long Island, New York, between October 2014 and January 2015. Ovarian fecundity ranged from 0 to 6 eggs, whereas uterine fecundity ranged from 0 to 7 embryos. The average ovarian fecundity and uterine fecundity were equal at 4.1, and fecundity increased with maternal body length. All ovarian eggs and embryos in an individual female were at the same stage of development. Ovarian eggs ( n  =   200) ranged from 1.4 to 4.9 cm in diameter and weighed between 1.3 and 39 g. Embryos ( n  =   200) ranged from 8.6 to 27.5 cm TL and weighed between 2 and 74 g. The sex ratio of the embryos (female : male) was 1.17:1.00; however, within individual females, one sex dominated over the other. The development of ovarian eggs was concurrent with embryo development. The data collected in this study can be used in future stock assessments for the northwest Atlantic Spiny Dogfish population.